A Clinical Profile and Co-morbidities of Pemphigus Vulgaris Patients: A Study of 35 Cases - Razzaque, Md Abdur; Ali, Zulfikar; Uddin, Kazi Shihab; Islam, Md Imtiajul; Nath, Sajib Kumar (KYAMC Journal, 2019)
Background: Pemphigus vulgaris (PV), an autoimmune blistering disease involving the skin and mucosa. PV frequently begins with oral lesions and progresses to skin lesions. Autoimmune bullous skin disorders are associated with IgG or IgA auto- antibodies against distinct adhesion molecules of the epidermis and dermal epidermal basement membrane zone, respectively. These auto- antibodies lead to a loss of skin adhesion which shows up clinically as the formation of blisters or erosions. Objectives: To characterize the clinical parameters and co-morbidities of PV patients from a single tertiary medical centre in Bangladesh. Material and Methods: This observational study was done including 35 PV patients attending in the department of Dermatology and Venereology, Khwaja Yunus Ali Medical College Khawja Eunus Ali Medical College from 2010 to 2014. Thirty patients of pemphigus diagnosed clinically confirmed and treated over a 4-year period (2010-2014). Results: Majority of the patients 45.7% belongs to age group 41-50 years. Mean age 47.12±11.13. The male to female ratio in our study sample was 1:1.5. The youngest patient was 17 years old and the oldest 68. For both genders, the risk of onset peaked during the fifth and sixth decade of life. Out of 35 patients, 15(42.9%) was presented with mucosal lesions only, while 13 patients 37.1% had mucocutaneous lesions and 7 patients 20% had only cutaneous lesions. The most common comorbidies were hypertension 20.0%, osteoporosis 17.1%, and diabetes 8.6%, thyroid disease 8.6%, psoriasis 5.7%, rheumatoid arthritis 2.7%, rheumatic fever 2.9%, autoimmune hepatitis 2.9%, and myasthenia gravis 2.9%. Conclusion: The associated comorbidities of PV emphasize the need for dermatologists to keep a high index of suspicion and actively evaluate patients to determine their presence. KYAMC Journal Vol. 10, No.-2, July 2019, Page 106-109